2018
DOI: 10.1002/brb3.1015
|View full text |Cite
|
Sign up to set email alerts
|

Neural functional architecture and modulation during decision making under uncertainty in individuals with generalized anxiety disorder

Abstract: BackgroundRecent evidence suggests that repetitive transcranial magnetic stimulation (rTMS) might be effective in treating generalized anxiety disorder (GAD). Cognitive models of GAD highlight the role of intolerance of uncertainty (IU) in precipitating and maintaining worry, and it has been hypothesized that patients with GAD exhibit decision‐making deficits under uncertain conditions. Improving understanding of the neural mechanisms underlying cognitive deficits associated with IU may lead to the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…We also checked that subsequent reports did not increase the J Psychiatry Neurosci 2021;46 (6) sample size, only adding secondary analysis to the original sample). [108][109][110][111][112] We excluded 1 paper because it did not include patients, 29 1 because it did not include patients with a diagnosis of an anxiety disorder, 112 1 because it did not test anxiety as an outcome measure, 113 and 1 because the full text was not available. 114 Figure 1 summarizes the selection procedure.…”
Section: Study Selectionmentioning
confidence: 99%
“…We also checked that subsequent reports did not increase the J Psychiatry Neurosci 2021;46 (6) sample size, only adding secondary analysis to the original sample). [108][109][110][111][112] We excluded 1 paper because it did not include patients, 29 1 because it did not include patients with a diagnosis of an anxiety disorder, 112 1 because it did not test anxiety as an outcome measure, 113 and 1 because the full text was not available. 114 Figure 1 summarizes the selection procedure.…”
Section: Study Selectionmentioning
confidence: 99%
“…One of the main theories of Generalized Anxiety Disorder (GAD) holds that intolerance of uncertainty (IU) plays the central role of a cognitive bias that interferes with information processing (including decision-making) 17 . According to the IU model, in the case of uncertainty, excessive emotional response is conducive to the development and maintenance of anxiety 18 . A study in a large sample of 1,092 young people also showed that IU has a significant moderating effect on the relationship between daily stress and worry 19 .…”
mentioning
confidence: 99%
“…Four records were excluded because they were conference proceedings (Assaf et al, 2017, 2014; Deppermann et al, 2013; Griffiths, O’Neill-Kerr, & De, 2019), two did not include patients (Ironside et al, 2019), one included patients but without a diagnosis of an anxiety-related disorder (Caulfield & Stern, 2020), and one did not test anxiety as an outcome measure (Heeren et al, 2017). Six studies were excluded because they did not consider a control condition, namely sham stimulation or a control group (Bystritsky et al, 2008; Clarke et al, 2019; Kumar, Singh, Parmar, Verma, & Kumar, 2018; Lu et al, 2018; Mantovani et al, 2007; White & Tavakoli, 2015), six because they involved samples already tested by one of the ten eligible papers (Assaf et al, 2018; S Deppermann et al, 2016; Saskia Deppermann et al, 2017; Diefenbach, Assaf, Goethe, Gueorguieva, & Tolin, 2016; Diefenbach et al, 2019; Praško et al, 2009). The full text of the remaining two studies was not available (He, Zheng, Cai, & Zou, 2011; Wu, Hu, Yu, Liu, & Wang, 2016).…”
Section: Resultsmentioning
confidence: 99%